Modeling Small Structural and Environmental Differences in Solids with 15N NMR Chemical Shift Tensors. Issue 10 (12th April 2021) - Wang, Luther; Elliott, Alexander B.; Moore, Sean D.; Beran, Gregory J. O.; Hartman, Joshua D.; Harper, James K.
Abstract: The ability to theoretically predict accurate NMR chemical shifts in solids is increasingly important due to the role such shifts play in selecting among proposed model structures. Herein, two theoretical methods are evaluated for their ability to assign 15 N shifts from guanosine dihydrate to one of the two independent molecules present in the lattice. The NMR data consist of 15 N shift tensors from 10 resonances. Analysis using periodic boundary or fragment methods consider a benchmark dataset to estimate errors and predict uncertainties of 5.6 and 6.2 ppm, respectively. Despite this high accuracy, only one of the five sites were confidently assigned to a specific molecule of the asymmetric unit. This limitation is not due to negligible differences in experimental data, as most sites exhibit differences of >6.0 ppm between pairs of resonances representing a given position. Instead, the theoretical methods are insufficiently accurate to make assignments at most positions. Abstract : Assigning shifts : Two theoretical methods are evaluated for their ability to assign 15 N shifts from solid‐state guanosine dihydrate to one of two independent molecules present in the unit cell. Both methods assign all shifts to correct positions but accurately assign to a specific independent molecule only 20 % of the time.